Pengaruh Slow Deep Breathing Terhadap Tekanan Darah Lansia Hipertensi Yang Mendapat Senam Lansia Di Wilayah Kerja Puskesmas Purwosari - Anugraheni, Meidilla Laili, Arina Maliya, A.Kep.M.Si., Med (2017)
Hypertension in the elderly more year increase. According to the Department of Health Houshold Survey on Health,hypertension was ranked first as the most degenerative disease that affects many. There are two kinds of treatment that can be done to treat hypertension, that is with pharmacological and non-pharmacological. As had been widely developed with non-pharmacological treatment, in addition to keeping the elderly from taking drugs, also can maintain the stability of metabolism in the elderly. Non-pharmacological treatment can be obtained by doing physical activity and slow deep breathing.This study aimed to determine the effect of slow deep breathing and exercise on blood pressure of elderly hypertensive elderly. This type of research is quantitative, research methods quasy experiment with the design of two group pre-testposttest controldesign.This research was conducted in Puskesmas Purwosari in April 2017. The research sample of 30 respondents to the sampling technique used purposivesampling.The research instrument used observation sheet blood pressure. Data processing techniques in this study using the Wilcoxon test. Results of research addressing the average systolic blood pressure of experimental group before being given treatment equal to 148,67 mmHg and 94,67 mmHg diastolic and mean systolic blood pressure after the experimental group were given treatment equal 141,33 mmHg diastolic and systolic 90,00 mmHg with significant value 0.001 and diastole 0.008 or p<0,05. The conclusion shows the influence of slow deep breathingon blood pressure of elderly hypertensive got exercise elderly in Puskesmas Purwosari. Keywords: slow deep breathing, the elderly, hypertension, elderly exercise